2018
DOI: 10.14419/ijet.v7i4.36.28145
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Perceived Exertion of Potential Avionics Male Students and Proposed Exercises to Decrease Strain

Abstract: As a student in Aviation, particularly in the field of Avionics, one has to actuate real life practical in real life aircraft. In the field of Avionics, the electrical and electronic racks are usually located in confined and constricted spaces in the cargo bay of the aircraft. To actuate works upon these spaces requires the student to crawl and be in physically stressful position for a predetermined period. If the student could not withstand these situations, then their practical workmanship would be poor. Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…According to several reports by authorities, pilots involved in the incidents were not able to input adequate forces (legs and hands) to yaw and move the helicopter sufficiently [17]. Harridon had studied the physical fitness of personnel involved in Aviation and Harridon had came out with physical methods to aid personnel or pilots in controlling their physical inputs especially the utilization of their legs [20]. Harridon had proposed Partial Squats, Step-Ups, and Calf Raises where these physical exercises would collectively decrease the strains in the legs of the aviation personnel and subsequently the reduction of strains would allow these individuals to control the movement of their legs in an efficient manner as minor pain or strain would not be an obstacle anymore [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to several reports by authorities, pilots involved in the incidents were not able to input adequate forces (legs and hands) to yaw and move the helicopter sufficiently [17]. Harridon had studied the physical fitness of personnel involved in Aviation and Harridon had came out with physical methods to aid personnel or pilots in controlling their physical inputs especially the utilization of their legs [20]. Harridon had proposed Partial Squats, Step-Ups, and Calf Raises where these physical exercises would collectively decrease the strains in the legs of the aviation personnel and subsequently the reduction of strains would allow these individuals to control the movement of their legs in an efficient manner as minor pain or strain would not be an obstacle anymore [20].…”
Section: Resultsmentioning
confidence: 99%
“…Harridon had studied the physical fitness of personnel involved in Aviation and Harridon had came out with physical methods to aid personnel or pilots in controlling their physical inputs especially the utilization of their legs [20]. Harridon had proposed Partial Squats, Step-Ups, and Calf Raises where these physical exercises would collectively decrease the strains in the legs of the aviation personnel and subsequently the reduction of strains would allow these individuals to control the movement of their legs in an efficient manner as minor pain or strain would not be an obstacle anymore [20]. Even if the pilots were not clad with strains within their legs, these physical exercises are beneficial as these exercises offer avenues to pilots to practice their controlling skills especially controlling the movement of their legs (from slow to moderate to fast and also from low intensity to high intensity).…”
Section: Resultsmentioning
confidence: 99%
“…Crews that had enormous experiences were able to identify the appropriate method to enhance their fitness level. Harridon had studied the realm of physical fitness in the field of Aviation and results of the study had shown that high level of physical fitness is important in maintaining safety and delivering outputs [16]. Harridon also stated that physical fitness is a continuous process that should be ingrained in one's culture [16].…”
Section: Figure 1 Our Research Methodologymentioning
confidence: 99%
“…It's imperative for those that operate flying machines be physically sound and able to withstand the rigors of flying. Harridon stated that there are physical exercises that could aid pilots and transform them into beings that are fit [4].…”
Section: Introductionmentioning
confidence: 99%